DNA repair and aging in basal cell carcinoma: a molecular epidemiology study. - Qingyi Wei; Genevieve M. Matanoski; Evan R. Farmer; Mohammad Hedayati; Lawrence I. Grossman (1993)
This molecular epidemiology study examines the DNA-repair capacities (DRCs) of basal cell carcinoma (BCC) skin cancer patients (88) and their controls (135) by using a plasmid/host-cell reactivation assay. In this assay UV-damaged expression vector plasmid is transfected into peripheral blood T lymphocytes from the subjects. The host-cellular repair enzymes repair the photochemical damage in the plasmid, and 40 hr later the plasmid-encoded reporter chloramphenicol acetyltransferase is measured. An age-related decline in this DRC, amounting to approximately 0.61% per yr occurred in the controls from 20 to 60 yr of age. Reduced DRC was a particularly important risk factor for young individuals with BCC and for those individuals with a family history of skin cancer. Young individuals with BCC repaired DNA damage poorly when compared with controls. As the BCC patients aged, however, differences between cases and controls gradually disappeared. The normal decline in DNA repair with increased age may account for the increased risk of skin cancer that begins in middle age, suggesting that the occurrence of skin cancer in the young may represent precocious aging. Patients with reduced DRCs and overexposure to sunlight had an estimated risk of BCC > 5-fold greater than the control group. Such a risk was even greater (10-fold) in female subjects.